The Responsiveness Principle and the Bureaucratic Dilemmas in Public Service Management (African Journal of Public Administration & Management, 2026)
A government that effectively and efficiently addresses its citizens' needs and expectations is a symbol of a healthy democracy. This is well achieved through citizen-centric approaches that prioritize the needs and experiences of individuals in the design of government services and policies.